2016
DOI: 10.1007/s40262-016-0387-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Glucocerebrosidase in Gaucher Patients Receiving Enzyme Replacement Treatment

Abstract: This was the first in vivo study to quantify the accumulated enzymatic activity in patients receiving ERT for GD1. It showed that intra-leukocyte activity at baseline and at 15 min post-perfusion could be used as a possible marker for therapeutic individualization in patients receiving ERT for GD1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A number of causes have been postulated for this low penetration of the exogenous enzyme into monocyte–macrophage of GD1 patients. These include different macrophage immunophenotypes , the high variability of the M6P receptor , the saturation of the mannose receptor at high doses or that the enzyme is eliminated by peptidases or outside of the vascular endothelium at a faster rate than the rate of uptake by the monocyte .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of causes have been postulated for this low penetration of the exogenous enzyme into monocyte–macrophage of GD1 patients. These include different macrophage immunophenotypes , the high variability of the M6P receptor , the saturation of the mannose receptor at high doses or that the enzyme is eliminated by peptidases or outside of the vascular endothelium at a faster rate than the rate of uptake by the monocyte .…”
Section: Discussionmentioning
confidence: 99%
“…High between‐subjects variability in the maximum activity achieved after the infusion into the leucocytes, which is later distributed throughout the organism (Act 75 ) could be due to the patients have different values of endogenous enzyme and because of the variability in the degree of exogenous enzyme uptake . Therefore, the amount of enzyme that comes from the ERT (Act 75‐0 ) in patients with OR is virtually the same amount as healthy individuals have of endogenous enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic enzyme is designed to be internalized by monocyte/macrophage through receptor‐mediated endocytosis via mannose receptors 37 . Therefore, the leukocyte enzymatic activity is considered the PK endpoint to predict the individual enzymatic activity 19 . Furthermore, GCase activity was measured in peripheral leukocytes because blood monocytes are a type of leukocyte and previous studies have shown GCase activity in monocytes represents 96% of total leukocyte approximately 38 …”
Section: Discusionmentioning
confidence: 99%